(untitled) (Economics and region, 2025)
This article explores the potential of Ukrainian tourism in the socio-economic integration of internally displaced persons (IDPs). It analyzes the current state of the internal displacement problem in Ukraine, which affects over 1.5 million registered IDPs. The main difficulties faced by displaced persons are discussed, including housing problems, high unemployment rates, low incomes, and psychological issues. The importance of developing the tourism industry as an effective tool for employment and economic activation of IDPs is substantiated. The potential of tourism in job creation, entrepreneurship development, intercultural exchange, and social cohesion is highlighted. International experience and programs supporting entrepreneurship among displaced persons are analyzed, which can be adapted to Ukrainian realities. Promising areas of involving IDPs in the tourism sector are identified, including rural green tourism, cultural tourism, gastronomic tourism, event tourism, and educational tourism. It is noted that tourism stimulates the development of infrastructure, which improves the general living conditions in the communities where IDPs are located. At the same time, tourism activities can help preserve and rethink cultural heritage, especially if IDPs are involved in its promotion and preservation. The involvement of internally displaced persons in all forms of tourism can open up new opportunities for sustainable development both for themselves and for the communities where they are located. That is, tourism can act as an effective platform for dialogue, integration, self-realization and economic growth for both internally displaced persons and the localities and communities where they are located. Recommendations are made for the effective implementation of socio-economic integration of IDPs through the development of Ukrainian tourism and entrepreneurship. These recommendations include the development of comprehensive support programs, the creation of a favorable business environment, the provision of financial support, and the organization of educational programs. The article also outlines prospects for further research in this area, including the development and evaluation of the effectiveness of specific programs to support tourism entrepreneurship among IDPs, the study of the long-term impact of involving IDPs in the tourism industry on the socio-economic development of host communities, as well as the study of the specifics of adaptation of different categories of IDPs in the tourism sector. The research results indicate a significant potential of the tourism industry in job creation, entrepreneurship development, and social adaptation of IDPs in new communities.